What is the Diagnosis? - Luz Leiria, Tiago Luiz; Pires, Leonardo Martins; Kruse, Marcelo Lappa; Lima, Gustavo Glotz de (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
We present a cases of iregular narrow QRS tachycardia in a young patient. We discuss the diagnostic possibilities for the tachycardia and it’s implication for the treatment.